In Silico Study of Aglycon Curculigoside A and Its Derivatives as α-Amilase Inhibitors - Nursamsiar Nursamsiar; Maya M. Mangande; Akbar Awaluddin; Syamsu Nur; Aiyi Asnawi (Indonesian Journal of Pharmaceutical Science and Technology, 2020)
α-amilase is an enzyme that catalyzes the hydrolysis of starch polysaccharides into oligosaccharides to then produce glucose. Inhibitions of the α-amylase enzyme is an effective strategy in modulating blood sugar levels in diabetics. The aglycon curculigoside A has similar structure to chalcon which is able to inhibit the α-amilase enzyme for the treatment of type 2 diabetes. The aim of this study was to determine the interaction of the curculigoside A aglycone compound and its derivatives with the α-amylase enzyme by using the docking simulation method. Docking simulations were carried out by using AutoDock 4.2 and α-amilase protein (PDB ID: 1B2Y) as macro molecule. The docking results showed that the aglycone curculigoside A and its derivatives able to interacted into the active site of the α-amylase enzyme. Three best ligands according to the simulation and prediction tests were compound 10, compound 23, and compound 41 has formed hydrogen bonding to Asp197, Glu233 and Asp300 residues with free bonding energy of -7.29, -7.22, dan -7.84 kcal/mol, respectively. In conclusion, Three best ligands has the same pattern of hydrogen bonds to the native ligand AC1 (6-methyl-5-(4,5,6-trihydroxy-3-hydroxymethyl-cyclohex-2-enylamino)-tetrahydro-pyran-2,3,4-triol) via amino acids redisues of α-amylase that play a role in the substrate by hydrolysis process.Keywords: aglycon curculigoside A, α-amylase, diabetes, docking